Education For Healthy Hydroponic Of Spinach Vegetable Without Pepticide To Fulfill The Nutritional Needs Of The Family Of Golong Village, Narmada District, West Lombok Regency - Karunia Nining Handaningrum; Tri Cahyani Widiastuti; Endang Yuniarti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The Muhammadiyah Aisyiyah Community Service Program (KKN Mas) in West Lombok was held to help solve the health problem faced today is stunting. One of the factors that cause stunting is the lack of adequate nutritional needs of children. Hydroponic plant education can be used to grow healthy vegetables without the use of chemicals / peptides to fulfill the nutritional needs of the family. This educational activity aims to provide knowledge to the people of the Golong Village in utilizing their yard for hydroponic vegetable cultivation to meet the nutritional needs of families. The method of implementing the activities are: Preparation and training of hydroponic plant cultivation. The training activities were attended by ten PKK cadres. The community gave a good and open response regarding the education provided. This is expected to help the community to improve understanding of the planting a simple hydroponic system.